The Analysis Study of Diagnostic Performance and Accuracy of Panoramic Radiography to Screen Bone Mineral Density in Woman: A Comprehensive Systematic Review - Audhi, Muhammad Riefki; Salsabila, Safira (International Medical Journal Corp. Ltd, 2024)
Background: Bone mineral density (BMD) is a crucial measure of bone health, providing essential information for assessing the risk of fractures and other bone-related conditions. Panoramic radiography, commonly used in dental practice, presents a potential alternative for BMD screening. This systematic to evaluate the effectiveness of panoramic radiography in detecting BMD based on literatures of the last 10 years Methods: The study adhered to PRISMA 2020 standards, examining English literature from 2014 to 2024. It excluded editorials, reviews from the same journal, and submissions without a DOI. PubMed, SagePub, SpringerLink, and Google Scholar were utilized as literature sources. Result: Initially retrieving 360 articles from online databases (PubMed, SagePub, SpringerLink and Google Scholar) eight relevant papers were selected after three rounds of screening for full-text analysis. Conclusion: Panoramic radiographs, including MI, MCI, and MCW, are valuable tools for screening bone mineral density (BMD) and detecting osteoporosis in women. Panoramic radiographs are effective in detecting osteoporosis, especially in postmenopausal women.